2018
DOI: 10.1007/s00408-018-0117-7
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Pneumonia and Hospital-Acquired Pneumonia: Bacterial Aetiology, Antibiotic Resistance and Treatment Outcomes: A Study From North India

Abstract: The patient characteristics in HCAP, treatment outcomes, bacterial aetiology, and a higher incidence of antibiotic-resistant bacteria, suggest that HCAP although not as severe as HAP, can be grouped as a separate third entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
3
0
2
Order By: Relevance
“…We found that patients’ background characteristics such as age; male sex; being underweight; residence in a nursing home or extended care facility; being bedridden; prior admission; immunosuppression; and comorbidities of heart failure, liver failure, and COPD, as well as severity of conditions at admission, including dehydration, respiratory failure, conscious disturbance, and hypotension were significantly associated with 30-day hospital mortality. These factors have been consistently reported in older studies in the late 1990s and in more recent studies [ [25] , [26] , [27] , [28] , [29] ]. Bedsores were further identified as an independent risk factor for mortality.…”
Section: Discussionsupporting
confidence: 65%
“…We found that patients’ background characteristics such as age; male sex; being underweight; residence in a nursing home or extended care facility; being bedridden; prior admission; immunosuppression; and comorbidities of heart failure, liver failure, and COPD, as well as severity of conditions at admission, including dehydration, respiratory failure, conscious disturbance, and hypotension were significantly associated with 30-day hospital mortality. These factors have been consistently reported in older studies in the late 1990s and in more recent studies [ [25] , [26] , [27] , [28] , [29] ]. Bedsores were further identified as an independent risk factor for mortality.…”
Section: Discussionsupporting
confidence: 65%
“…Despite improvements in prevention, antimicrobial therapy, and supportive care [30], HAP remains an important cause of morbidity and mortality. HAP has been associated with significant mortality [31,32]. In our study, IHM was similar in COPD patients and in non-COPD patients, with no significant change overtime.…”
Section: Discussionsupporting
confidence: 60%
“…HAP can have negative consequences for patients, including prolonged hospital stay, decreased quality of life and high mortality [6,7]. Despite improvements in prevention, antimicrobial therapy, and supportive care [1], HAP remains an important cause of morbidity and mortality [8]. The mortality rate for HAP ranges from 38% to more than 70% [9].…”
Section: Introductionmentioning
confidence: 99%